2014
DOI: 10.1177/1049731514540478
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Therapeutic Alliance With Children in Residential Treatment and Therapeutic Day Care

Abstract: Purpose: This study examined the construct validity and reliability of a therapeutic alliance measure (Children's Alliance Questionnaire [CAQ]) for children with psychosocial and/or behavioral problems, receiving therapeutic residential care or day care in the Netherlands. Methods: Confirmatory factor analysis of a one-factor model ''therapeutic alliance'' was conducted on two samples of 115 and 116 children, aged 4-14 years. Reliability analysis and concurrent validity were examined. Results: Results showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The understanding of these transactional processes is necessary to stimulate professional behavior by staff (Van der Helm and Stams 2012). Negative transactional processes (as opposed to positive transactional processes, such as establishing a working alliance; Roest et al 2014) may occur between the youth and the staff because of fear, mechanisms of dehumanization, lack of empathy, and rationalization. At the next level, staff members and team leaders influence each other because of the identification and socialization processes.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of these transactional processes is necessary to stimulate professional behavior by staff (Van der Helm and Stams 2012). Negative transactional processes (as opposed to positive transactional processes, such as establishing a working alliance; Roest et al 2014) may occur between the youth and the staff because of fear, mechanisms of dehumanization, lack of empathy, and rationalization. At the next level, staff members and team leaders influence each other because of the identification and socialization processes.…”
Section: Discussionmentioning
confidence: 99%
“…Schubert et al (2012) found positive effects on young people's behaviour when the living group climate was non-coercive (see also Parhar et al, 2008) and Leeman et al (1993) showed that an institutional group intervention based on justice and a positive peer culture can promote socio-moral development and decrease recidivism (see also Van Stam et al, 2014). Furthermore, the institutional climate or living group climate may have influence whether an adolescent reduces antisocial behaviour through accepting an alliance with group workers (Bouffard and Piquero, 2010;Roest et al, 2014;Schubert et al, 2012). Recently, Hoogsteder et al (2014) conducted a quasi-experimental study in a secure juvenile justice institution and found that violent offenders' irrational cognitions, poor coping skills, aggression and recidivism risk were reduced and treatment motivation enhanced by a responsive and non-punitive living group climate that targeted the specific needs of the individuals those incarcerated.…”
Section: Secure Residential Treatmentmentioning
confidence: 99%
“…The quantitative results of the Prison Group Climate Instrument (PGCI) (Author's own ), the Group Climate Instrument (GCI) (Strijbosch et al, ), the Children's Alliance Questionnaire (CAQ; Roest, Van der Helm, Strijbosch, Van Brandenburg, & Stams, ), and the Adolescence Treatment Motivation Questionnaire (ATMQ; Author's own, ) were summarized, and scale results were calculated. In preparation of the group meetings, the project leader analysed the outcomes.…”
Section: Outline Of the Projectmentioning
confidence: 99%
“…In this questionnaire, five report scores needed to be given: the support by the group workers, things to be learned, the atmosphere in the unit/group, the honesty and the rules in the unit. Possible answers range from 1 ( very bad ) to 10 ( very good ). The Children's Alliance Questionnaire (CAQ 4–8 [10 questions] and 8–12/15 [nine questions]; Roest et al, ) documents the alliance between the individual group worker and the child. Items include My individual group worker understands me; My individual group worker has time to spend with me; … Possible answers to the subscales in the questionnaire CAQ (4–8) range from 1 ( totally not agree ) to 3 ( agree ).…”
Section: Implications Of the Projectmentioning
confidence: 99%